FAMILY RESILIENCE AMONG FARMERS IN THE GALESONG DISTRICT - muh nurikhsan; najamuddin; Supriadi Torro (SOSIOEDUKASI, 2025)
This study analyzes the factors influencing farming family resilience and strategies developed to strengthen it in Galesong District, Takalar Regency. Farming family resilience has become a critical issue considering the agricultural sector's vulnerability to price fluctuations, climate change, and limited capital access. The study employed a qualitative approach with a case study design conducted in East Galesong Village. Informants were selected through purposive sampling, consisting of farming families as primary informants, along with the village head and farmer group leader as supporting informants. Data were collected through in-depth interviews and documentation studies, then analyzed using the Miles and Huberman model. The findings reveal that farming family resilience is influenced by five interacting dimensions: family integrity with strong emotional bonds and zero divorce rates, economic resilience through livelihood diversification, physical resilience with adequate food access, socio-psychological resilience built through religious values and emotional communication, and socio-cultural resilience supported by mutual cooperation traditions. The developed strategies encompass four approaches: active coping through income diversification and agricultural intensification, planning through planting schedule and financial planning, seeking instrumental social support through farmer groups and mutual cooperation, and seeking emotional social support through family support and religious activities. The combination of these five resilience dimensions with four adaptive strategies creates a resilience system enabling farming families to survive despite structural limitations.